The politics of direct democracy : referendums in global perspective - LeDuc, Lawrence (CEL - Canadian Publishers Collection., 2003)
"Considering its growing popularity among many political reformers, the referendum remains much understudied. This book aims to provide a comprehensive, up-to-date survey of direct democratic institutions and devices as they have developed both in the thinking of modern political theorists and in actual political practice in the world's major democratic nations. Among the cases specifically considered are the California and Swiss models, the two Quebec sovereignty referendums, the 1999 Australian referendum on the monarchy, the 2000 Danish referendum on the Euro, Irish referendums on divorce and abortion, and the votes in Sweden on nuclear energy and European Union membership."--